Exploring the formation of 'Black Widows' - Benvenuto, Omar Gustavo (2015)
Black Widows (BWs) are a class of binary millisecond pulsars orbiting together with very low mass donor stars (≲ 10-2M⊙). After the discovery of eclipses in the first known BW, PSR 1957+20, they are considered as close binary systems (CBSs) in which the donor star is being evaporated by the radiation emitted by the pulsar. Standard CBS evolution calculations (i.e. without evaporation) have faced serious difficulties when trying to find ways to form BWs. When the donor star is in Roche Lobe Overflow conditions after becoming semi-degenerate, it will evolve to longer orbital periods as a consequence of its swelling reaction to mass loss. In order to reach orbital periods in the range observed for several BWs, it would need to spend times far in excess of the age of the Universe. Here we extend the calculations presented in our previous papers on the topic, including evaporation, showing that the evolution of CBSs with a neutron star component together with an intermediate-mass, normal star provides a successful and natural scenario to account for the existence and properties of BWs.